Trends in dyslipidemia prevalence among Uyghur adults of different genders in China: a retrospective cohort study - Maimaitituersun, Gulinigaer; Jureti, Subinuer; Yi, Ziyu; Zhou, Yaqi; Li, Meng; Wei, Mengwei; Liu, Ziyang; Jin, Menglong; Fu, Zhenyan (PeerJ, 2025)
Background To analyze the prevalence and epidemiological characteristics of dyslipidemia among adults of different genders in Xinjiang, China, providing a basis for promoting ideal lipid management among the Uyghur population. Methods In this retrospective study, we included 7,646 Uyghur adults from the 2021 physical examination data in Hotan, Xinjiang, and followed up with all participants in 2023 for analysis. Participants completed lifestyle and medical history questionnaires and underwent lipid profiling. Dyslipidemia was defined according to the 2023 Chinese guidelines for lipid management. Group differences were analyzed using t-tests, ANOVA, and chi-square tests, the trend test for ordered categorical variables was conducted using univariate linear regression, and multivariable logistic regression was performed to explore risk factors for dyslipidemia. Results In 2023, the average levels of waist circumference, fasting glucose, total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and non-HDL-C among Uyghur men and women, as well as the prevalence of diabetes, increased compared to 2021, with significant statistical differences within the same gender groups (P < 0.001). The primary types of dyslipidemia among Uyghur adults were low HDL-C. After age and gender standardization, the overall standardized prevalence of high low-density lipoprotein cholesterol (LDL-C), hypertriglyceridemia, and low HDL-C showed a downward trend, with a more pronounced decrease among men. The prevalence of hypercholesterolemia and high non-HDL-C increased from 2021, with a greater increase among women. In 2023, the standardized prevalence rates of hypercholesterolemia, high LDL-C, low HDL-C, hypertriglyceridemia, and high non-HDL-C were higher in women than in men. Multivariable logistic regression adjusted for multiple factors indicated that higher educational attainment (OR 1.992; 95% CI [1.042–3.808]; P = 0.037), overweight (OR 1.303; 95% CI [1.085–1.566]; P = 0.005), obesity (OR 1.520; 95% CI [1.226–1.886]; P = 0.000), and central obesity (OR 1.013; 95% CI [1.006–1.021]; P = 0.001) were associated with dyslipidemia in Uyghur men, while in Uyghur women, dyslipidemia prevalence was mainly related to obesity (OR 1.549; 95% CI [1.261–1.902]; P = 0.000) and central obesity (OR 1.009; 95% CI [1.002–1.016]; P = 0.01). Conclusion The primary forms of dyslipidemia among Uyghur adults include low HDL-C levels. The prevalence of high LDL-C, hypertriglyceridemia, and low HDL-C is showing a declining trend, particularly among men. In contrast, the prevalence of hypercholesterolemia and high non-HDL-C is increasing more significantly among women. In men, risk factors for dyslipidemia include higher educational attainment, being overweight, obesity, and central obesity. In women, the prevalence of dyslipidemia is mainly associated with obesity and central obesity.
Keywords: Dyslipidemia; Hypertriglyceridemia; Low HDL-C; Non-HDL-C; Uyghur